VALES – III. The calibration between the dust continuum and interstellar gas content of star-forming galaxies. (27th February 2017) - Hughes, T. M.; Ibar, E.; Villanueva, V.; Aravena, M.; Baes, M.; Bourne, N.; Cooray, A.; Davies, L. J. M.; Driver, S.; Dunne, L.; Dye, S.; Eales, S.; et al.
Abstract: We present the calibration between the dust continuum luminosity and interstellar gas content obtained from the Valparaíso ALMA Line Emission Survey (VALES) sample of 67 main-sequence star-forming galaxies at 0.02 < z < 0.35. We use CO(1–0) observations from the Atacama Large Millimetre/submillimetre Array to trace the molecular gas mass, M H 2, and estimate the rest-frame monochromatic luminosity at 850 μm, L_ν _850, by extrapolating the dust continuum from magphys modelling of the far-ultraviolet to submillimetre spectral energy distribution sampled by the Galaxy And Mass Assembly survey. Adopting αCO = 6.5 (K km s −1 pc 2 ) −1, the average ratio of L_ν _850 / M H 2 = (6.4 ± 1.4)× 10 19 erg s −1 Hz −1 M_^-1, in excellent agreement with literature values. We obtain a linear fit of _10 (M_H_2/M_) = (0.92± 0.02) _10 (L_ν _850/erg s^-1 Hz^-1)-(17.31± 0.59) . We provide relations between L_ν _850, M H 2 and M ISM when combining the VALES and literature samples, and adopting a Galactic αCO value.